Cryogenian Glacial Habitats as a Plant Terrestrialisation Cradle – The Origin of the Anydrophytes and Zygnematophyceae Split - Žárský, Jakub; Žárský, Vojtěch; Hanáček, Martin; Žárský, Viktor (Frontiers in Plant Science, 2022)
For tens of millions of years (Ma), the terrestrial habitats of Snowball Earth during the Cryogenian period (between 720 to 635 Ma before present – Neoproterozoic Era) were possibly dominated by global snow and ice cover up to the equatorial sublimative desert. The most recent time-calibrated phylogenies calibrated not only on plants but on a comprehensive set of eukaryotes indicate that within the Streptophyta, multicellular charophytes (Phragmoplastophyta) evolved in Mesoproterozoic to early Neoproterozoic. At the same time, Cryogenian is the time of likely origin of the common ancestor of Zygnematophyceae and Embryophyta and later also of the Zygnematophyceae – Embryophyta split. This common ancestor is proposed to be called Anydrophyta; here, we use anydrophytes. Based on the combination of published phylogenomic studies and estimated diversification time comparisons, we deem highly likely that anydrophytes evolved in response to Cryogenian cooling. Also, later in the Cryogenian, secondary simplification of multicellular anydrophytes and loss of flagella resulted in Zygnematophyceae diversification as an adaptation to the extended cold glacial environment. We propose that the Marinoan geochemically documented expansion of first terrestrial flora has been represented not only by Chlorophyta but also by Streptophyta, including the anydrophytes, and later by Zygnematophyceae, thriving on glacial surfaces until today. It is possible that multicellular early Embryophyta survived in less abundant (possibly relatively warmer) refugia, relying more on mineral substrates, allowing retention of flagella based sexuality. The loss of flagella and sexual reproduction by conjugation evolved in Zygnematophyceae and zygomycetous fungi during the Cryogenian in a remarkably convergent way. Thus, we support the concept that the important basal cellular adaptations to terrestrial environments were exapted in streptophyte algae for terrestralization in streptophyte algae and propose that this was stimulated by the adaptation to glacial habitats dominating the Cryogenian Snowball Earth. Including the glacial lifestyle when considering the rise of land plants increases the parsimony of connecting different ecological, phylogenetic and physiological puzzles of the journey from aquatic algae to the terrestrial floras.